A pilot study on the feasibility and effectiveness of treadmill-based perturbations for assessing and improving walking stability in chronic obstructive pulmonary disease. (January 2022) - McCrum, Christopher; Vaes, Anouk W.; Delbressine, Jeannet M.; Koopman, Maud; Liu, Wai-Yan; Willems, Paul; Meijer, Kenneth; Spruit, Martijn A.
Abstract: Background: Falls risk is elevated in chronic obstructive pulmonary disease (COPD). However, there is a lack of evidence regarding the contributing factors. Here, we examined the feasibility of, and initial responses to, large walking perturbations in COPD, as well as the adaptation potential of people with COPD to repeated walking perturbations that might indicate potential for perturbation-based balance training in COPD. Methods: 12 participants with COPD undergoing inpatient pulmonary rehabilitation and 12 age-gender-matched healthy control participants walked on an instrumented treadmill and experienced repeated treadmill-belt acceleration perturbations (leading to a forward balance loss). Three-dimensional motion capture was used to quantify the stability of participants body position during perturbed walking. Feasibility, stability following the initial perturbations and adaptation to repeated perturbations were assessed. Findings: Using perturbations in this manner was feasible in this population (no harness assists and participants completed the minimum number of perturbations). No clear, specific deficit in reactive walking stability in COPD was found (no significant effects of participant group on stability or recovery step outcomes). There were mixed results for the adaptability outcomes which overall indicated some adaptability to repeated perturbations, but not to the same extent as the healthy control participants. Interpretation: Treadmill-based perturbations during walking are feasible in COPD. COPD does not appear to result in significant deficits in stability following sudden perturbations and patients do demonstrate some adaptability to repeated perturbations. Perturbation-based balance training may be considered for fall prevention in research and practice in people with COPD. Highlights: Treadmill-based gait perturbations are feasible in people with COPD. People with COPD do not show large deficits in reactive gait stability. People with COPD demonstrate some but reduced adaptability to perturbations. Perturbation-based balance training may be considered for people with COPD.